PREDICTIVE FACTORS OF POST EXTRACORPOREAL SHOCK WAVE LITHOTRIPSI COMPLICATION EVENTS - Yuniarso, Fajar Nugroho; Tranggono, Untung (Indonesian Urological Association, 2017)
Objective: To know if pre-morbid factors such as maximum power, maximum frequency, repeated extracorporeal shock wave lithotripsy (ESWL), age, hypertension, diabetic, nutrition, blood coagulation disorders, kidney function disorders, pain perception, stone burden, and stone location, can be use to predict ESWL complication. Material & methods: This study is done retrospectively. Analysis was done on 50 patients undergoing ESWL between July 2014 to December 2015. Free variables which evaluated were maximum power, maximum frequency, repeated ESWL, age, hypertension, diabetic, nutrition, blood coagulation disorders, kidney function disorders, pain perception, stone burden, and stone location. Dependent variable which evaluated was steinstrasse event, post ESWL fever, post-ESWL renal colic, post-ESWL hematuria. Age variable were distributed normally and done bivariate analysis by student T-test. Others were abnormally distributed and analyzed univariately by Mann U Whitney. Results: During study period, 50 patients were collected. Among them, 60% were men and 40% were women. Mean age of patients undergo ESWL were 50.9 +12.7 years. Mean stone size that undergo ESWL were 172.7 + 277.8 mm2. Patients with hypertension before ESWL were 9 patients. Stones were mostly located on kidney pyelum (29 patients), inferior calix (11 patients), superior calix (5 patients), middle calix (4 patients), and 1 patients has staghorn stone. After ESWL, none of the patients complaining severe pain, 35 patient complaining mild pain, and 15 patient complaining moderate pain. Repeated ESWL done in 16 patients (32%). Post-ESWL complication such as hematuria happened on 12 patients, steinstrasse on 1 patient, and colic on 6 patients. None of patients complaining fever. Repeated ESWL happened on 32% patients and have complication risk of hematuria (p=0.043). Hypertension is significantly effecting on hematuria event after ESWL (p=0.015). Conclusion: Hypertension and repeated ESWL can be used as predicting factor of hematuria complication.